2019
DOI: 10.1002/wnan.1580
|View full text |Cite
|
Sign up to set email alerts
|

Integration of gadolinium in nanostructure for contrast enhanced‐magnetic resonance imaging

Abstract: Magnetic resonance imaging (MRI) is a routinely used imaging technique in medical diagnostics, which is further enhanced with the use of contrast agents (CAs). The most commonly used CAs are gadolinium‐based contrast agents (GBCAs), in which gadolinium (Gd) is chelated with organic chelating agents (linear or cyclic). However, the use of GBCA is related to toxic side effect due to the release of free Gd3+ ions from the chelating agents. The repeated use of GBCAs has led to Gd deposition in various major organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 65 publications
(146 reference statements)
2
50
0
Order By: Relevance
“…Currently, the most widely used MRI CAs are gadolinium (Gd 3+ ) chelates (Marasini et al, 2020). By using high-field MRI, Gd 3+ chelates can demonstrate the Aβ plaque imaging both ex vivo and in vivo (Sillerud et al, 2013).…”
Section: Commonly Used Mri Casmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most widely used MRI CAs are gadolinium (Gd 3+ ) chelates (Marasini et al, 2020). By using high-field MRI, Gd 3+ chelates can demonstrate the Aβ plaque imaging both ex vivo and in vivo (Sillerud et al, 2013).…”
Section: Commonly Used Mri Casmentioning
confidence: 99%
“…Due to the long electron spin-lattice relaxation time and abundant unpaired electrons (seven) per Gd 3+ ion has, the relaxation rate of water hydrogen can be increased significantly. However, ionic gadolinium complexes can leak toxic Gd 3+ ions with short half-life and it has been reported that Gd 3+ chelates can lead to renal insufficiency (Rashid et al, 2016;Marasini et al, 2020). Fluorinated small molecules that bind to amyloid plaques can be detected by 19 F MRI (Jirak et al, 2019).…”
Section: Commonly Used Mri Casmentioning
confidence: 99%
“…DOX loading was quantified spectrophotometrically at excitation and emission wavelengths of 490 nm and 580 nm following the published protocol. 38,42 The results showed that the initial DOX loading can be precisely tuned by varying the drug input (10,25,50,100,150,200, 300, and 400 mg mg À1 of PLGA weight) during the NP preparation process. Among the different initial DOX feeding concentrations, the maximum encapsulation efficiency of the control NP was found to be about 93% ( Fig.…”
Section: Physiochemical Characterization Of Npsmentioning
confidence: 99%
“…7 Regardless of their complex structure, these lipid-polymer composite nanoparticles (NPs) are synthesized in a simple, single-step fashion, which allows future scale-up in production and cost-effective real-life applications. 1,[7][8][9][10][11][12] It has been established that the functionalization of polymer end groups and subsequent conjugation with targeting motifs such as peptides as a nanoparticle vehicle is a powerful strategy to permit precise drug delivery to the targeted site, while reducing systemic toxicities. 13 The use of the Food and Drug Administration (FDA) approved polymeric biomaterial, polyethylene glycol (PEG), as a surface passivating layer on the nanoparticle prevents aggregation, opsonization, and phagocytosis, and prolongs the systemic circulation time to improve the nanoparticle-based drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation contribution is quantitatively determined by the location between water protons and contrast agent. Water molecules coordinated to paramagnetic center will contribute to the inner sphere relaxation contribution and bulk water molecules will be responsible for the outer sphere relaxation (Ni et al, 2017;Marasini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%